HUBUNGAN TINGKAT TOKSISITAS LOGAM TIMBAL (Pb) DENGAN GAMBARAN SEDIAAN APUS DARAH PADA PEROKOK AKTIF - Betti Rosita; Helvina Mustika (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
Based on the results of a survey conducted by the World Health Organization (WHO) in 2012, the number of active smokers in the world has reached more than 1 billion people. This number is expected to continue to increase given the high prevalence of world cigarette consumption rates, while in Indonesia it is found that almost every year the number of smokers is increasing. Cigarettes containing chemicals including carbon monoxide, nicotine, tar, ammonia, arsenic, cyanide and lead (Pb) The main effect is lead that is inhaled and enters the respiratory system will also circulate throughout the tissues and organs of the body. More than 90% of lead metal absorbed by blood binds to red blood cells and results in a disruption in the process of hemoglobin synthesis. The purpose of this study is to determine the level of lead metal toxicity with an overview of smear preparations in the blood of active smokers. The research method with simple random sampling, samples taken capillary blood and making blood smear preparations that were examined with a microscope while examining the metal in the urine using Atomic Absorption Spectrophotometer (AAS). The results of the study of lead content in urine of active smokers found that the high is 0.384 mg / dl and the low lead level is 0.002 mg / dl positive containing lead in the urine with the amount of lead content exceeding the threshold and from the results of the smear dosage found that normal or normociter cell size can be obtained normal or normochrome (1/3 of the center is pale) whereas abnormalities in the cell form are teardrop cells, ovalocytes, schistocyte, this is due to the effect of lead that disrupts health especially usually occurs in haemotopoetic systems (blood formation system)